Attending live sporting events predicts subjective wellbeing and reduces loneliness - Keyes, Helen; Gradidge, Sarah; Gibson, Nicola; Harvey, Annelie; Roeloffs, Shyanne; Zawisza, Magdalena; Forwood, Suzanna (Frontiers in Public Health, 2023)
This study explored whether attending live sporting events (LSEs) improved subjective wellbeing and loneliness, above and beyond demographic predictors. Methods: Secondary data from 7,249 adults from the Taking Part 2019-20 survey (UK household survey of participation in culture and sport) were analysed. Multiple linear regressions captured the effect of attending LSEs (yes/no) on wellbeing variables (happiness, anxiety, a sense that life is worthwhile and life satisfaction) and loneliness, with gender, Index of Multiple Deprivation (IMD), age group, health and employment as covariates. Results: For life satisfaction, a sense that life is worthwhile, and loneliness, inclusion of LSE in the model improved model fit significantly (ΔR2 .001 to .003). For happiness and anxiety, the inclusion of LSE did not alter model fit. LSE was associated with increased life satisfaction (b=.171, p<0.001), a sense of life being worthwhile (b=.230, p<0.001), and reduced loneliness (b=-.083, p<0.01), with coefficients comparable with demographic predictors (e.g., being in employment). Conclusion: LSE attendance has a positive association with subjective wellbeing and loneliness, above and beyond demographic predictors. Promoting LSE attendance could offer a scalable, accessible and effective means to improve wellbeing and reduce loneliness.